The Colossian syncretism the interface between Christianity and folk belief at Colossae - Arnold, Clinton E. (Grand Rapids, MI Baker, 1996)
Includes bibliographical references and index.
This book first appeared 1995 as volume 77 in Wissenschaftliche Untersuchungen zum Neuen Testament, 2d series.
Keywords: Bible. N.T. Colossians -- criticism, interretation, etc; Angel worship